(untitled) (Journal of Training and Development, 2019)
The purpose of the study was to develop and validate the Worked Examples to enhance the instructors’ competencies in carrying out technology integration during teaching and learning. Worked Examples in the study was developed based on the Gagne’s Nine Event of Instruction, which is one of the classroom-oriented micro level Instructional Design Models. Technology integration in the study is defined as an implementation of technological resources and pedagogical strategies to deliver the required content knowledge during classroom instruction. Thus, Technological Pedagogical and Content Knowledge (TPACK) was integrated in the developed Worked Examples. Development and Design research design was implemented to develop and validate the Worked Examples, employing qualitative and quantitative data, where three instructors from Teacher Education Program utilized Worked Examples during their classroom instruction. Extraneous cognitive load of instructors found to be addressed because of employing Worked Examples. Furthermore, pre-service teachers learning outcomes was also significantly improved because of instructors’ instructions with Worked Examples.